2002
DOI: 10.1007/s005920200027
|View full text |Cite
|
Sign up to set email alerts
|

Insulin-resistant patients with type 2 diabetes mellitus have higher serum leptin levels independently of body fat mass

Abstract: In obese people, an increase of plasma leptin levels is well-known and is seen as a consequence of the increased body fat mass. Moreover, a relationship between fasting concentrations of leptin and insulin has been described. Hyperinsulinemia is considered to be indicative of insulin resistance. We aimed at elucidating the interrelations between leptin, insulin and insulin resistance in type 2 diabetic patients. Under metabolic ward conditions, we investigated 21 moderately overweight men with type 2 diabetes.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
86
0
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 138 publications
(93 citation statements)
references
References 27 publications
4
86
0
1
Order By: Relevance
“…For example, although men with insulin-resistant type 2 diabetes may initially have increased levels of endogenous insulin, IGF-1 and leptin, as the disease progresses to insulin deficiency (the stage where insulin may be added as a therapy), levels of these factors decrease. 10,17,18 Insulin and IGF-1 may be involved in prostate cancer development through stimulating cell growth and proliferation. 11,15 Other factors, such as circulating leptin, have also been implicated in the development and progression of prostate cancer.…”
Section: Discussionmentioning
confidence: 99%
“…For example, although men with insulin-resistant type 2 diabetes may initially have increased levels of endogenous insulin, IGF-1 and leptin, as the disease progresses to insulin deficiency (the stage where insulin may be added as a therapy), levels of these factors decrease. 10,17,18 Insulin and IGF-1 may be involved in prostate cancer development through stimulating cell growth and proliferation. 11,15 Other factors, such as circulating leptin, have also been implicated in the development and progression of prostate cancer.…”
Section: Discussionmentioning
confidence: 99%
“…While previous reports have indicated a relationship between leptin levels and insulin resistance, this relationship has been considered by some to be due to increased fat mass (21). Other investigators have demonstrated both in experimental animals and in human subjects that the association between insulin resistance and leptin levels may be independent of body fat mass (22,23). Leptin can also inhibit insulin-stimulated glucose uptake in cultured rat skeletal muscle cells (24).…”
Section: Resistinmentioning
confidence: 99%
“…IGF1 is part of an inter-related metabolic system that includes insulin and two adipocytokines (leptin and adiponectin) that are closely related with insulin (Fischer et al 2002, Matsubara et al 2002, Stefan et al 2002, Wauters et al 2003. It has been shown that insulin has a role in breast cancer incidence through stimulation of proliferation of breast cancer cells (Milazzo et al 1992, Mayer et al 2008.…”
Section: Introductionmentioning
confidence: 99%